Social and philosophy understanding of «upbringing» and «education» (Journal of Philosophy Culture and Political Science, 2018)
The article is devoted to comparative consideration of terminology in the field of upbringing and education in Slavic, English and some other European languages. Comparison of an internal form and terminological field of words allows to draw conclusions about uniqueness of the Russian concept «upbringing» among languages of Europe. Key words: paideia, education, upbringing, internal form, mentality, language picture of the world.